Psychological and Physiological Changes in Response to the Cumulative Demands of a Women's Division I Collegiate Soccer Season. Issue 5 (3rd May 2022) - McFadden, Bridget A.; Walker, Alan J.; Bozzini, Brittany N.; Hofacker, Morgan; Russell, Mark; Arent, Shawn M.
Abstract: McFadden, BA, Walker, AJ, Bozzini, BN, Hofacker, M, Russell, M, and Arent, SM. Psychological and physiological changes in response to the cumulative demands of a women's division I collegiate soccer season. J Strength Cond Res 36(5): 1373–1382, 2022—This study sought to determine the effects of a women's collegiate soccer season on psychological markers, biomarkers, sleep, and performance. Athletes participated in maximal countermovement vertical jump height (CMJ) assessments and biomarker monitoring in conjunction with subjective measures of psychological wellness and sleep questionnaires before preseason (S1) and every 4 weeks following (S2, S3, and S4). Training was monitored during practices and games using global positioning satellite systems and heart rate technology. Total training load was highest from S1 to S2, decreased from S2 to S3 (effect size [ES] = -2.5; p < 0.001), and remained stable from S3 to S4. CMJ declined at S2 (ES1-2 = −0.51; p = 0.001) and returned to baseline at S3. Increases from S1 to S2 were seen for creatine kinase (ES1-2 = 1.74), free testosterone (ES1-2 = 1.27), total testosterone (ES1-2 = 3.5), and free cortisol (ES1-2 = 0.88) ( p < 0.03) before returning to baseline by S3 and S4 (free cortisol). Total cortisol was elevated throughout the season before declining at S4 (ES1-4 = −0.41; p = 0.03). Iron declined from S1 to S2 (ES1-2 = −0.73; p = 0.01) and returned to baseline values at S4, whereas growth hormone declined at S2 (ES1-2 = −0.50; p = 0.01) and remained depressed. Interleukin-6 increased at S4 (ES1-4 = 0.71; p = 0.02). Total training distress decreased from S1 to S2 (ES1-2 = −0.38; p = 0.02), returned to baseline by S3, and increased by S4 (ES1-4 = 0.57; p = 0.01). No changes were observed in markers of sleep ( p > 0.05). Biomarkers showed notable changes after the highest workload period (S1-S2), which coincided with CMJ decrements. Biomarker perturbations preceded declines in subjective psychological wellness (S4) which occurred in the latter half of the season, indicating an accumulation of fatigue as the season progressed.